Behavioural Aspects in Property Market Research - Mar Iman, Abdul Hamid (Nil, 2009)
This chapter discusses the fundamental elements of human behaviour that are involved in real estate decision-making. It discusses among other things definition of behaviour, elements of behaviour, model of buying process, decision-making process, and some application of behavioural aspects in property market research.